THE PERCEPTION OF ISLAMIC RELIGIOUS EDUCATION STUDENTS ON KAHOOT! AS A QUIZ - Ilmudinulloh, Rafiud (IJIET (International Journal of Indonesian Education and Teaching), 2023)
Kahoot! is the most popular online platform in universities to increase student participation in class. The application is suggested as an instrument for the assessment of learning outcomes. This study aims to determine the level of perception of Islamic religious education students towards Kahoot! as a quiz in the midterm exam. The research approach used is descriptive qualitative with questionnaire and observation data collection techniques. The data were then analyzed using descriptive statistics by presenting the data in the form of tables and diagrams. Based on the results of the study, it can be concluded that students' perceptions are very positive in terms of three main indicators, namely the ease of understanding how the application works, the ability of the application to involve participants, and the relevance of quizzes to learning activities. Most students think that Kahoot! provide new experiences that are interesting, fun, and challenging. They are motivated and actively participate in taking quizzes.